Factors Influencing Consumer Intention to Purchase Organic Food in Ubon Ratchathani Province, Thailand - Chaiyakarn Zheng, Jiaranai; Nakornchaigul, Kamonphon (Dusit Thani College Journal, 2020)
The trend of consuming organically produced food is highly determined by market demand both domestically and internationally. Therefore, this research aims to reflect on consumers’ perceptions and attitudes influencing consumer intention to purchase organic food in Ubon Ratchathani province, Thailand. This research gathers on a survey of 385 respondents in seven difference places where organic food is sold in town. Organic food buyers are majorly female who concentrates in the working age population from 31 years to 50 years old but occasional buyers tend to be younger with age below 31 years old. Results indicate that the two primary reasons to purchase organic food are an expectation of having a healthier and environmentally friendly means of production. Frequent organic buyers tend to have better education, higher income and are more likely to have at least one infant at home. Furthermore, organic vegetable and fruit, rice and herbal drinks are most highly demanded. However, the lack of knowledge towards organically produced food is one of the major obstacles to increase the market share of organic food in Thailand.